Discriminatory, yet socially accepted? Targets’ perceptions of subtle and blatant expressions of ethno-racial prejudice - Stanke, Franziska A.; Kuper, Niclas; Fetz, Karolina; Echterhoff, Gerald (Frontiers in Social Psychology, 2024)
Introduction Extant research has studied prejudice expressions mainly from the majority perspective. We examined whether prejudice expressions conceptualized as subtle (vs. blatant) are perceived differently by their targets. Methods Participants who self-identified as potential targets of ethno-racial or religious prejudice (e.g., anti-Muslim, anti-Asian, anti-Arab, anti-Slavic, and anti-Black prejudice), answered questions about verbal expressions of prejudice taken from the subtle and blatant prejudice scales in an online survey. Results Items of the subtle (vs. blatant) prejudice scale were rated as more socially accepted and less discriminatory, elicited less negative emotions, and were reported to be experienced more often. Subtle expressions of prejudice were not more familiar to participants than blatant ones. Remarkably, blatant prejudice expressions were also perceived as relatively socially accepted and subtle prejudices as relatively discriminatory, as indicated by mean ratings above the scale midpoint. Lower discrimination ratings of subtle (vs. blatant) prejudice expressions were mainly due to perceptions of expressions exaggerating cultural differences. Exploratory analyses indicate that participants who reported more (vs. less) frequent overall exposure to the prejudice expressions perceived subtle and blatant stimuli as similarly discriminatory. This finding is compatible with the idea that individuals factor their personal experiences with prejudice into their assessments of discrimination. Discussion We discuss implications for interventions, especially regarding the social acceptability of blatant prejudice and promoting awareness of the discriminatory impact of subtle prejudice.